Molybdenum tungsten disulphide (MoWS2) as a saturable absorber for a passively Q-switched thulium/holmium-codoped fibre laser. Issue 11 (25th June 2019) - Ahmad, H.; Sharbirin, A. S.; Ismail, M. F.
ABSTRACT: In this work, a passively Q-switched Thulium/Holmium-doped fibre laser (THDFL) using a molybdenum tungsten disulphide (MoWS2 ) saturable absorber (SA) is proposed and demonstrated. The MoWS2 nanosheets are prepared by hydrothermal exfoliation and then suspended in a polyvinyl alcohol (PVA) thin film host. Q-switching of the THDFL at a maximum 1550 nm pump power of 445.2 mW gives a maximum repetition rate and minimum pulse width of 36.3 kHz and 2.8 µs with a corresponding pulse energy of 86.4 nJ and peak power of 31.1 mW. The MoWS2 based Q-switched THDFL's output has a very high signal-to-noise value of ∼62.2 dB which strongly indicates that the laser is working in a stable operation. To the best of our knowledge, this is the first demonstration of MoWS2 as a passive SA in a THDFL for operation in the 2.0 µm region. The proposed laser would have significant medical and sensing applications, particularly at the biologically active 2.0–2.1 µm regions.